Albuminuria, glycemic variability and effect of flash glucose monitoring based decision making on short term glycemic variability in Indian type 2 diabetes patients: Indi-GlyVar study - Nathiya, Deepak; Singh, Mahaveer; Suman, Supriya; Bareth, Hemant; Pal, Nikita; Jain, Arjav; Tomar, Balvir S. (Frontiers in Endocrinology, 2022)
Aim and Scope: Glycemic variability (GV) denotes the fluctuations in the glucose values around the baseline. High glycemic variability is associated with a higher risk of diabetes-associated complications. In this study, we sought to determine the impact of therapeutic interventions based on flash glucose monitoring on rapid, short-term glycemic variability. We also studied the prevalent albuminuria diabetic kidney disease and its effect on glycemic variability. Methods: In a 14-day, single-centre, prospective intervention study, we measured the GV indices at baseline (days 1-4) and ten days after ambulatory glucose profile-based intervention using Abbott freestyle libre pro flash glucose monitoring (FGM) in patients with type 2 diabetes. The primary outcome was to assess the impact of FGMS-based therapeutic interventions on glycemic variability markers-: SD, MAGE, CONGA, MODD, M value, and coefficient of variance [%CV], AUC< 70 mg/dL, LBGI, AUC > 180, HBGI, and J index. Time-related matrices [TIR (%), TAR (%), and TBR(%)] were also calculated from the ambulatory glucose profile. Renal function parameters were calculated. The GV with regard to albumin excretion rate was compared. Results: Fifty-nine T2DM patients (63.8%, Males) with a mean age of 51.5±11.9 years were studied. When compared with baseline (days 1-4), on day fourteen, there was a significant improvement in mean sensor glucose (mg/dl) median(IQR) [155 (116-247) vs 131 (103-163) (p=<0.001)], JINDEX [15878 (7706-28298) vs 8812 (5545-14130) (p=<0.001)], HBGI [361 (304-492) vs 334 (280-379) (p=<0.001)], MAGE (mg/dl) [112 (8-146) vs 82 (59-109) (p=<0.001)], M-value [2477 (1883-3848) vs 2156 (1667-2656) (p=<0.001)], MAG (mg/dl) [111 (88-132) vs 88 (69-102) (p=<0.001)]. Patients with albuminuria at baseline had high mean sensor glucose(mg/dl) median(IQR) [190(131-200) vs 131 (112-156) (p=0.001)], CONGA (mg/dl) median(IQR) [155(101-165)vs108(83-120) (p=0.001)], JINDEX, HBGI, MAGE (mg/dl), and M-value are, median(IQR)[20715 (10970-26217 vs 91118 (6504-15445)) (p=<0.01)], [415 (338-423) vs 328 (292-354) (p=0.001)], [125(102-196)vs103(74-143) (p=<0.01)], [3014 (2233-3080) vs 2132 (1788-2402) (p=<0.01)] respectively. Conclusion: In type 2 diabetes, flash glucose monitoring-guided therapeutic interventions can reduce glycemic variability in a very short span (10 days) of time. Also, albuminuria in type 2 diabetes is associated with high glycemic variability. Reduced diabetes complications may ultimately occur from this reduced glycemic variability.